Evaluation of Bio-diesel Produced from Used-Frying Oil on a Diesel Engine - Susilo, Bambang (Jurnal Teknologi Pertanian, 2006)
Used-frying oil in snack and fast foods industries was considered as a waste and the amount grows along with the industries. It still contains a high level of energy, but its   viscosity and flash point is relatively high that make it is not suitable for diesel engine fuel. Moreover, the used-frying oils mostly contains suspended as well as moisture. This research was performed to evaluate the characteristics of the bio-diesel made up of such oil by a trans-esterification process on a diesel engine in a comparison with the normal diesel fuel. The results showed that the engine power run with bio-diesel was 4.14% higher than did with the normal diesel fuel.  However, it was observed that the bio-diesel consumption was 9.5% higher than that of the normal diesel fuel for a specified diesel engine running.   Keywords: used-frying oil, trans-esterification, bio-diesel